Tomato post-harvest fruit ripening in Pakistan : effect of methylcyclopropene (1-MCP) in inhibiting ripening gene expression - Ramzan, Aleena; Javed, Rida; Zulfiqar, Alveena; Shakeel, Samina N. (Universiti Kebangsaan Malaysia, 2022)
Short shelf life of tomato fruits, with the unavailability of modernized handling/storage and transport practices causes ~30-40 % of yield loss which leads to great financial burden on the import of Pakistani tomatoes. There is an urgent need to adapt an easy and cost effective applicable technology for increasing the shelf life of fully ripened tomato fruits by inhibiting ethylene perception that leads to ripening and decay. This study aims to evaluate the effectiveness of ethylene perception inhibitor 1-methylcyclopropene (1-MCP) on ripening of tomatoes. Physiological and molecular parameters were recorded to analyse the inhibitory effect of 1-MCP. Green tomatoes were harvested and treated with 1-MCP for 24 h and 8 days. Results of the physiological data based on colour, weight, and firmness of the fruits showed a significant delay in the onset of ripening after 1-MCP treatment. 1-MCP is known to block ethylene receptors, therefore, we used different ethylene and ripening related genes as markers to prove that 1-MCP potentially delayed tomato fruit ripening by inhibiting the ethylene pathway that in turn downregulated the ripening signalling pathway genes. Therefore, this study provides evidence that 1-MCP can effectively be used as an alternative to reduce the post-harvest tomato yield losses in Pakistan with slight optimization on the method to suit the different varieties of local tomatoes.